The complete guide to wiring : current with 2020-2023 electrical codes. (Cool Springs Press, an imprint of The Quarto Group, 2021)
The Complete Photo Guide to Wiring is BLACK+DECKER's eighth edition of the best-selling home improvement book in North America for more than a decade, now completely updated to conform to 2021-2024 National Electrical Code.